Analisis Posisi Bersaing dan Strategi Bauran Pemasaran untuk Meningkatkan Jumlah Kunjungan Pada Handara Golf and Resort di Bedugul Bali - Rosalia Nita Aryani; Ni Made Rustini; Taman Sari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2020)
This research to determine the competitive position based on the Boston Consulting Group matrix, to find out internal variables including strengths and weaknesses as well as external variables including opportunities and threats and to find out relevant marketing mix strategies to increase the number of visits. The study was conducted at Handara Golf and Resort in Bedugul Bali. Data analysis techniques used are the Boston Consulting Group matrix analysis and SWOT analysis. The analysis shows that using BCG matrix analysis, the company is in the position of dogs with a growth rate of 7.09% and an analysis of market share of 0.17. Using a SWOT analysis shows that the most dominant external opportunity variable with the acquisition of 3.80 results. Where the opportunity indicator is an increase in the number of tourists, growth in online sales, buyers want more images in electronic commerce or e-commerce when buying a product, most of the time on mobile devices is used, social media plays a major role in the distribution of most of the time used on mobile devices, technological advances over the use of social media, per capita income growing in Indonesia, located in the Pacific Ring of Fire, new regulations from Bank Indonesia. While the threat indicator is providing alternative tourist attractions throughout Indonesia to tourists other than in Bali and losing followers in the social media, it can be concluded that companies need to implement a turn-around strategy because external opportunities are more oriented to supporting the company's Handara Golf and Resort Bali.